Strength performance of lightweigt concrete using bead as aggregate - Mohd Hashim, Nor Fazilah (2008)
Research is being carried out to study the strength performance of lightweight concrete made from crystal plastic bead aggregates. The bead aggregates were used to replace gravels in concrete mix. The replacement was based on a different percentages varying from 20% to 100%. A control normal weight concrete containing 100% gravels aggregate was prepared. All of the materials were prepared in accordance to as weight basis and based on the Building Research Establishment’s method. Concrete with beads as coarse aggregate was investigated for workability and cube compressive strength after 7days and 28days curing. The results indicated that lightweight concrete mix with beads reduced approximately 20% of mass compared to conventional normal weight concrete. The highest compressive strength achieved for 28days was found to be 24 N/mm2 with 20% of bead replacement which is lower than target strength of 30 N/mm2. However, the compressive strength value was within the normal concrete range for structural purposes. In short, increased amount of bead in concrete mix may reduce the compressive strength of concrete and increased the workability of fresh concrete.